Impact of Hybrid Learning on Digital Literacy and Mathematical Resilience in Master's Mathematics Education - Lala, Laelasari; Maharani; Setiyani; Kharimah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
Higher education in mathematics faces challenges in simultaneously building digital literacy and mathematical resilience. The limited number of studies integrating both aspects in a hybrid context remains a research gap. This study aims to evaluate the impact of hybrid learning on the digital literacy and mathematical resilience of master's students in mathematics education. A qualitative study with an instrumental case study design was conducted in the Master's Program in Mathematics Education at a university in Cirebon City, Indonesia. Data were collected through semi-structured interviews, observations of hybrid learning, and analysis of digital documents from nine students. Data analysis was conducted using Braun & Clarke's thematic analysis approach, which includes six stages: data familiarization, initial coding, theme identification, review, naming, and narrative writing, supported by method triangulation, inter-coder validation, and member checking to maintain credibility. Results showed improvements in digital literacy across technical (100%), evaluative (78%), and creative (67%) aspects. Mathematical resilience also improved through persistence (100%), cognitive flexibility (89%), and emotional regulation (78%). The hybrid environment was found to facilitate the simultaneous strengthening of students' technical, affective, and reflective skills. These findings contribute theoretically and practically to the development of a hybrid curriculum that promotes digital literacy while building students' mathematical resilience.